Altered glucocorticoid reactivity and behavioral phenotype in rx3-/- larval zebrafish - Herget, Ulrich; Ryu, Soojin; De Marco, Rodrigo J. (Frontiers in Endocrinology, 2023)
Mutant animals lacking the transcription factor rx3 have been well characterized in developmental studies, but relatively little is known about their behavioral phenotypes. Consistent with their role in hypothalamus and pituitary development, here we show a distinct loss of corticotrope cells involved in stress regulation, severe reduction of pituitary innervation by hypothalamic cells, and lack of stress-induced cortisol release in rx3 mutants. Interestingly, despite these deficits, we report that rx3-/- larval zebrafish can still display nominal behavioral responses to both stressful and non-stressful stimuli. However, unlike wildtypes, mutants lacking proper pituitary-interrenal function do not show enhanced behavioral performance under moderate stress level, supporting the view that corticotroph cells are not required for behavioral responses to some types of stressful stimuli but modulate subtle behavioral adjustments under moderate stress.